Dynamics of the ulnar nerve after percutaneous pinning of supracondylar humeral fractures in children - Belhan, Oktay; Karakurt, Lokman; Ozdemir, Huseyin; Yilmaz, Erhan; Kaya, Mehmet; Serin, Erhan; Inci, Murat (Lippincott Williams & Wilkins, 2009)
This prospective study was performed to evaluate and compare the morphological changes and dynamics of the ulnar nerve after percutaneous cross-pinning with Kirshner wire (group 1; 13, mean age 8.3 years, 10 male and three female children) and only lateral pinning (group 2; eight, mean age 7.6 years, six male and two female children) of displaced unilateral supracondylar fractures in children's elbows using ultrasonography in comparison with the contralateral healthy elbows. Postoperative evaluation revealed that ulnar nerve movement was reduced and the major axis diameter of elbow flexion and ulnar nerve was larger (P<0.05) than the major axis diameter in the elbow extension in group 1 than group 2. We think that the treatment of the displaced supracondylar fracture of the humerus in children with only a lateral Kirshner wire would be safer and more convenient. J Pediatr Orthop B 18:29-33 (C) 2009 Wolters Kluwer Health Lippincott / Williams & Wilkins.
Keywords: children; crossed Kirshner wire; lateral Kirshner wire; percutaneous pinning; supracondylar humerus fractures